Linoleic and linolenic acids analysis of soybean tofu with Rhizopus oryzae and Rhizopus oligosporus as coagulant - CICIK SUDARYATININGSIH; SUPYANI SUPYANI (Nusantara Bioscience, 2009)
Abstract. Sudaryatiningsih C, Supyani. 2009. Linoleic and linolenic acids analysis of soybean tofu with Rhizopus oryzae and Rhizopus oligosporus as coagulant. Nusantara Bioscience 1: 110-116. The aims of this research are to know the potency of Rhizopus oligosporus and Rhizopus oryzae as a coagulant in tofu processing for increasing the amount of linoleic and linolenic acids, and to know the time that needed by R. oligosporus and R. oryzae for increasing the amount of linoleic and linolenic acids. It uses PDA for inoculating fungi, and it is done at Sub-Lab Chemistry, Central Laboratory for Mathematics and Natural Sciences, Sebelas Maret University, Surakarta. The tofu making was done in “Dele Emas” Tofu Factory, Surakarta. Analysis of linoleic and linolenic acids was done by Gas Chromatography, in LPPT-UGM Yogyakarta. The conclusion of this research is R. oligosporus dan R. oryzae having a potency as a coagulant in tofu processing for increasing the amount of linoleic and linolenic acids. R. oryzae needs 18 hours to coagulate the tofu, and R. oligosporus requires 12 hours for the same process. R. oryzae obtained the highest amount of linoleic and linolenic acids. R. oryzae at 6 hours of fermentation (0.26% and 0.14%), and 24 hours of fermentation by R. oligosporus (0.06% and 0.04%).